A clinical study on the surgical management of intestinal obstruction - Gogineni, Jyotsna Choudary; Tonape, Trupti; Athavale, V. S.; Kumar, Sree; Kutty, Shweta Achuthan; Sri Likhita, K. (International Surgery Journal, 2019)
Background: Intestinal obstruction remains one of the common emergencies encountered by general surgeons all over the world. Acute intestinal obstruction occurs when there is a disruption in the frontward flow of intestinal contents. Methods: This study is a prospective study conducted in Dr. D Y Patil Medical College and Hospital, Pimpri, Pune. Patients coming to the hospital with signs and symptoms suggestive of intestinal obstruction and willing for surgical management in our hospital were included after taking written and informed consent. Results: In our study, pain abdomen and abdominal distension was the most common presenting complaints in 90% and 92% of the patients respectively. On palpation, 96% of the patients had abdominal tenderness, 72% of the patients had guarding and 12% of the patients had rigidity. On auscultation, all patients had some abnormality with regard to bowel sounds. It has been noted that intestinal strictures and abdominal adhesions were amongst the most common causes of intestinal obstruction in our study. Conclusions: Prompt clinical assessment aided by radiological imaging is of crucial importance in reaching the diagnosis of intestinal obstruction. Decision regarding surgical intervention is taken based on the initial presentation of the patient, and his/her response to first line conservative management and fluid resuscitation